Endoplasmic Reticulum Stress and Mitochondrial Function in Airway Smooth Muscle - Delmotte, Philippe; Sieck, Gary C. (Frontiers in Cell and Developmental Biology, 2020)
Asthma affects more than 20 million people in the USA, and more than 300 million people world-wide. It is now recognized that inflammation triggers asthma pathophysiology, and involves mediators such as Tumor Necrosis Factor α (TNFα). While a number of cell types (e.g., airway epithelium and immune cells) likely play roles in asthma, airway smooth muscle (ASM) is a key player by contributing to both exaggerated airway narrowing via enhanced [Ca2+]cyt and force responses to agonist stimulation (i.e., “hyper-contractile” state) as well as to increased ASM cell proliferation (i.e., “proliferative” state). An emergent theme in this context is the role of inflammation-induced endoplasmic reticulum (ER) stress and mitochondrial function. A major feature of asthma is an increase in reactive oxygen species (ROS) generation, and in other cell types, it has been shown that excess ROS generation leads to ER stress. It is unclear whether inflammation-induced ROS is the major mechanism leading to ER stress. In various diseases, inflammation leads to an increase in mitochondrial fission, associated with decreased expression of mitochondrial fusion proteins, such as mitofusin 2 (Mfn2). Mitochondrial fission is generally coupled with mitochondrial biogenesis and cell proliferation. Some studies in other cell types suggest that mitochondrial fission may be a result of the accumulation of unfolded or misfolded proteins, i.e., ER stress, which induces a homeostatic response to restore normal ER function by halting protein translation and promoting protein degradation and expression of molecular chaperones involved in protein folding. However, previous studies have suggested that Mfn2 and altered mitochondrial dynamics are not downstream but upstream to ER stress such that a reduction in Mfn2 triggers ER stress. In this review, we summarize the current state of understanding of the link between inflammation-induced ER stress and mitochondrial function and the role played in airway disease pathophysiology, identifying areas of unmet research need, and opportunities for novel therapeutic strategies.